2014
DOI: 10.1080/00380768.2014.975103
|View full text |Cite
|
Sign up to set email alerts
|

Radiocesium transfer into the fruit of deciduous fruit trees contaminated during dormancy

Abstract: Following the accident at the Tokyo Electric Power Company, Fukushima Daiichi Nuclear Power Plant (FDNPP), radiocesium ( 134 Cs + 137 Cs) concentrations in deciduous mature fruits were determined in orchards in the northern area of Fukushima Prefecture. At the time of the nuclear accident, most deciduous fruit trees were in the dormant stage prior to bud burst. To evaluate the relationship between radiocesium deposition in the soil and fruit contamination, radiocesium concentrations were measured from the 5-cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…There were roots of undergrowth running through the topsoil at a high density because sod culture was applied in almost all orchards in Fukushima Prefecture. Therefore, radiocaesium contamination by root uptake was likely negligible during the accident year (Sato et al, 2015), the same as in a previous report in relation to the Chernobyl accident (AntonopoulosDomis et al, 1991). Deposits on the scaffold trunk of peach, cherry, apple, Japanese pear, and grape trees were recognized by measuring the radiation count rate using Geiger-Mueller survey meter at 1 cm distance from the bark surface at the top, side, and bottom sites on the scaffold limb 30 cm from a bifurcation on April 28, 2011 (Sato, 2012).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…There were roots of undergrowth running through the topsoil at a high density because sod culture was applied in almost all orchards in Fukushima Prefecture. Therefore, radiocaesium contamination by root uptake was likely negligible during the accident year (Sato et al, 2015), the same as in a previous report in relation to the Chernobyl accident (AntonopoulosDomis et al, 1991). Deposits on the scaffold trunk of peach, cherry, apple, Japanese pear, and grape trees were recognized by measuring the radiation count rate using Geiger-Mueller survey meter at 1 cm distance from the bark surface at the top, side, and bottom sites on the scaffold limb 30 cm from a bifurcation on April 28, 2011 (Sato, 2012).…”
Section: Introductionsupporting
confidence: 61%
“…Small fruit volume may result in high 137 Cs content at an early stage. On the other hand, the 137 Cs concentration in fruits decreases by the dilution effect of assimilates transported into fruits in the ripening stage (Sato et al, 2015). In addition, the effects of bark washing on decreasing the Cs from leaves to fruits in the ripening stage (Carini and Bengtsson, 2001).…”
Section: Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the TFs, calculated using the radiocesium concentrations of the fruit and soil (0-15 cm) in the intertillage plots, were 0.013 in 2011, 0.0017 in 2012, 0.00050 in 2013, and 0.00031 in 2014. In the early years of 2011-2014, the TFs in apples may have been affected by the direct adhesion of fallout-derived radiocesium (Kusaba et al, 2015a, b;Sato, 2014;Sato et al, 2015); however, direct radiocesium adhesion might have had a smaller effect on the TF value in 2014. In 2014, the TF values of apples in this study are almost the same as those observed in herbaceous fruit.…”
Section: Discussionmentioning
confidence: 99%
“…AntonopoulosDomis et al (1991) demonstrated that the root uptake of radiocesium represented a small fraction of the total contamination of leaves and fruit of trees planted before the Chernobyl accident. Sato et al (2015) also suggested that the amount of radiocesium uptake via the roots of fruit trees was negligible after the FDNPP accident. On the other hand, Takata et al (2013) reported that, with a high concentration of radiocesium in the surface soil, the transfer rate of radiocesium from the soil to plants was higher in the shallow-rooted fruit tree fig than in the non-shallow-rooted fruit tree grape, suggesting that the radiocesium uptake via the roots of fruit trees could not be negligible under experimental conditions.…”
Section: Introductionmentioning
confidence: 99%